2022
DOI: 10.3389/fimmu.2021.830018
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Exosomal circRNAs Contribute to Potential Diagnostic Value of Large Artery Atherosclerotic Stroke

Abstract: Large artery atherosclerotic (LAA) stroke is closely associated with atherosclerosis, characterized by the accumulation of immune cells. Early recognition of LAA stroke is crucial. Circulating exosomal circRNAs profiling represents a promising, noninvasive approach for the detection of LAA stroke. Exosomal circRNA sequencing was used to identify differentially expressed circRNAs between LAA stroke and normal controls. From a further validation stage, the results were validated using RT-qPCR. We then built logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Similar results were found in another study based on exosomal circRNA. Our experiment showed that exosomal circRNA could be used as a more efficient diagnostic marker for LAA stroke; much more interestingly, we found that exosomal circRNA could predict vulnerable plaques 153 . Our studies have demonstrated the potential of exosomal non-coding RNAs as biomarkers.…”
Section: Macrophage-associated Exosomes In Arteriosclerosismentioning
confidence: 62%
“…Similar results were found in another study based on exosomal circRNA. Our experiment showed that exosomal circRNA could be used as a more efficient diagnostic marker for LAA stroke; much more interestingly, we found that exosomal circRNA could predict vulnerable plaques 153 . Our studies have demonstrated the potential of exosomal non-coding RNAs as biomarkers.…”
Section: Macrophage-associated Exosomes In Arteriosclerosismentioning
confidence: 62%
“…RNA isolation and quantification were carried out as previously described [26]. The Supplementary Materials went into detail about these specifics and Methods and primers used for the genes of interest are listed in Supplementary Table S1.…”
Section: Rna Isolation and Quantificationmentioning
confidence: 99%
“…To assess H3K4me2, Chromatin immunoprecipitation (ChIP) assays were carried out in accordance with the manufacturer's instructions (26,156; Thermo Scientific) [29]. The details were described in the Supplementary Materials and Methods and primers used for the genes of interest are listed in Supplementary Table S3.…”
Section: Chromatin Immunoprecipitation (Chip)mentioning
confidence: 99%
“…The nomogram also revealed the potential predictive value of exosomal circRNAs in plaque instability. Besides this, they suggested that these two exo-circRNAs exerted a protective role in ischemic stroke, as a negative correlation between their expression and the NIHSS scores was found [ 21 ]. Considering that this was a single-center study, future multicenter studies are needed to validate these results and avoid selective bias.…”
Section: The Potential Diagnostic Value Of Exosomal Noncoding Rnas In...mentioning
confidence: 99%